ROLAND BARTHES'S SEMIOTIC ANALYSIS OF THE PLAASTRO METHOD - Jerry Dounald Rahajaan (JURNAL PAKARENA, 2021)
The PlaAstro method applied at K - PAS Indonesia as one of the teaching methods for special children emphasizes closeness in the arts. With suppressed visuals from gestures and expressions, the PlaAstro method can be read theoretically from the perspective of Roland Barthes Semiotics.The PlaAstro method, which is embodied in Roland Barthes' Semiotics perspective, has become an aesthetic journey of Fahdi Hasan, Str.Sn in responding to his critical thinking on discrimination and community idealism for people with disabilities (special individuals) through the Special Child Care Community (K - PAS Indonesia).